(untitled) (Homoeopathy for All, 2025)
Homeopathy was introduced in India the early 19th century. It flourished in Bengal at first, and then spread all over India. In the beginning, the system was extensively practised by amateurs in the civil and military services and others. Mahendra Lal Sircar was the first Indian who became a homeopathic physician. A number of allopathic doctors started homeopathic practice following Sircar’s lead. The ‘Calcutta Homeopathic Medical College’, the first homeopathic medical college was established in 1881. This institution took on a major role in popularising homeopathy in India.